Effect of non-specific cervico-vaginal infections in the perinatal outcomes in women with preterm labor - V. N. Kuzmin (Лечащий Врач)
The article presents a retrospective study of the history of preterm birth and perinatal outcomes. Statistical analysis of the effect of non-specific cervico-vaginal infections in the perinatal outcomes was performed.